Voltage and evolutionary piezoelectric actuator design optimisation for static shape control of smart plate structures - Nguyen, Quan; Tong, Liyong (Materials in engineering, 2007)
This paper presents an iterative technique for multi-criteria design problem in structural shape control applications, which consist of voltage and piezoelectric actuator criteria designs based on the linear least square (LLS) method and the evolutionary piezoelectric actuator design optimisation (EPADO), respectively. The criterion identifies the overall effects of the error function on these two components of design criteria due to removing active piezoelectric materials. Two algorithms are proposed. One is the alternative voltage and evolutionary piezoelectric actuator design optimisation (AVEPADO). Another is voltage and evolutionary piezoelectric actuator design optimisation (VEPADO). Both algorithms aim to simultaneously optimise the active piezoelectric actuator configuration and the applied voltage. Numerical results are presented to show that the proposed algorithms are capable of determining both voltage distribution and piezoelectric actuators configuration in structural shape control problems.